Development of E-Jisha Mobile Learning Application of Japanese Vocabulary For JLPT N5 Students: E-Jisho - Omar, Hasnifa Syarmilla; KAMARUDIN, DR. NORAZIAHTULHIDAYU KAMARUDIN (Applied Information Technology And Computer Science, 2026)
Foreign languages have been practiced in Malaysia for a long time as a third language. Learning a foreign language is beneficial in many ways, as it can be used for various purposes. Japanese language has become one of the popular foreign languages that is learned by the Malaysian community nowadays, even though the language itself is challenging to learn. The existing application to learn the Japanese language that has been studied is too generalized, does not focus too much on the beginner learner, and is not beginner-friendly. Therefore, this project aimed to develop a game-based learning application named E-Jisho, which offered simple but detailed lessons and enjoyable gameplay that can help users improve Japanese vocabulary and reading skills by using Multimedia Mobile Content Development (MMCD) methodology. This project’s target user is JLPT N5 student who wants to take the examination and people who are beginners in learning the Japanese Language. This application is expected to help the target user learn and memorize Japanese words and vocabulary with relaxing and enjoyable gameplay methods.